Investment motives and preferences – An empirical inquiry during COVID-19 - Riyazahmed K. (Investment Management & Financial Innovations, 2021)
Following the COVID-19 breakout, investment in shares, mutual funds, and life insurance are witnessing a growing trend in India. Hence, examining the determinants of investor preferences is necessary to maintain a positive trend. This study analyzes the impact of investor motives and awareness on investor preferences using the data collected from 753 Indian investors in 2020. Factor analysis grouped the investment motives into six categories, namely Nature of investments, Future financial needs, Investor personal characteristics, Safety and stability of investments, Investor behavioral aspects, and Investor’s options. The regression model used to find the impact of the investment motives and the awareness on the investor preferences explains 52.3% of changes in investor preference. Investment factors like Nature of investments, Investor personal characteristics, Investor behavior, Investor options, Awareness of mutual funds, and shares have a significant impact on investor preferences. Further, the awareness level of mutual funds and the stock market are the major variables contributing to Investors’ preference rather than identified investment factors. Investors’ personal characteristics like knowledge, confidence, ability, responsibility, and belief negatively influence investor preferences. This study adds to the existing literature by analyzing investment motives and preferences during the pandemic.